Isolation rate and drug resistance patterns of Shigella species among diarrheal patients attending at Hiwot Fana Hospital, Harar, Ethiopia - Mekonnen, H; Kebede, A; Menkir, S (Ethiopian Journal of Science and Technology, 2025)
Over the past decades, Shigella species have shown a pattern of steady increase in resistance to antibiotics; and strains of Shigella have progressively become resistant to most of the widely used antimicrobial agents and even new antibiotics. A cross sectional study was conducted in Hiwot Fana Hospital, Harar, from February to May 2011 to determine the prevalence of Shigella species and their antimicrobial resistance patterns among diarrheal patients. Structured questionnaires were used to collect socio-demographic and other variables from patients/parents or guardians. A total of 384 stool samples were collected and cultured on MacConkey agar and xylose-lysine desoxycholate agar. Of the 384 stool specimens analyzed, 56 (14.6%) proved to be positive for Shigella species. All Shigella isolates were sensitive to ciprofloxacin while most were resistant to tetracycline (96.4%). Multiple drug resistance as many as to five antibiotics was detected. Lack of education, absence of regular hand washing habit, use of water from unprotected sources and absence of latrine were the risk factors that were associated with contracting Shigella species. High prevalence of Shigella spp. with multiple antibiotic resistance isolates were observed in this study. Ciprofloxacin may be used as a drug of choice for empirical treatment for Shigella infections. Regular, systematic monitoring of diarrheal cases is also needed to identify changes in the prevalence and antimicrobial resistance patterns of Shigella species.